Preliminary Photochemical Screening on the Leaf Extract of Eupatorium triplinerve Vahl - Sugumar, N (International Journal of Pharmaceutical & Biological Archive, 2015)
Preliminary Photochemical Screening on the Leaf Extract of Eupatorium triplinerve Vahl